Cardiac phenotype in ATP1A3-related syndromes: A multicenter cohort study. (24th November 2020) - Balestrini, Simona; Mikati, Mohamad A.; Álvarez-García-Rovés, Reyes; Carboni, Michael; Hunanyan, Arsen S.; Kherallah, Bassil; McLean, Melissa; Prange, Lyndsey; De Grandis, Elisa; Gagliardi, Alessandra; Pisciotta, Livia; Stagnaro, Michela; et al.
Abstract : Objective: To define the risks and consequences of cardiac abnormalities in ATP1A3 -related syndromes. Methods: Patients meeting clinical diagnostic criteria for rapid-onset dystonia-parkinsonism (RDP), alternating hemiplegia of childhood (AHC), and cerebellar ataxia, areflexia, pes cavus, optic atrophy, and sensorineural hearing loss (CAPOS) with ATP1A3 genetic analysis and at least 1 cardiac assessment were included. We evaluated the cardiac phenotype in an Atp1a3 knock-in mouse (Mashl +/− ) to determine the sequence of events in seizure-related cardiac death. Results: Ninety-eight patients with AHC, 9 with RDP, and 3 with CAPOS (63 female, mean age 17 years) were included. Resting ECG abnormalities were found in 52 of 87 (60%) with AHC, 2 of 3 (67%) with CAPOS, and 6 of 9 (67%) with RDP. Serial ECGs showed dynamic changes in 10 of 18 patients with AHC. The first Holter ECG was abnormal in 24 of 65 (37%) cases with AHC and RDP with either repolarization or conduction abnormalities. Echocardiography was normal. Cardiac intervention was required in 3 of 98 (≈3%) patients with AHC. In the mouse model, resting ECGs showed intracardiac conduction delay; during induced seizures, heart block or complete sinus arrest led to death. Conclusions: We found increased prevalence of ECG dynamic abnormalities in all ATP1A3 -related syndromes, with a risk of life-threatening cardiac rhythm abnormalities equivalent to that in established cardiac channelopathies (≈3%). Sudden cardiac death due to conduction abnormality emerged as a seizure-related outcome in murine Atp1a3 -related disease. ATP1A3 -related syndromes are cardiac diseases and neurologic diseases. We provide guidance to identify patients potentially at higher risk of sudden cardiac death who may benefit from insertion of a pacemaker or implantable cardioverter-defibrillator.